ASSESSORIA ECONÔMICO-GERENCIAL PARA EMPRESAS INDUSTRIAIS DA REGIÃO DE ATUAÇÃO DA UNIJUÍ – 2010 - Muenchen, José V.; Macagnan, Roberto; Kohler, Romualdo; Gregori, Cleidi D.; Mattana, Diogo M. (Salão do Conhecimento, 2013)
Resumo